Prevention of mens rea corruption of prospective legislators in Indonesia from a psychological perspective - ARDI PUTRI, M; SAPTOMO, A (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe purpose of this study is to analyze how to prevent mens rea corruption candidates for legislators in Indonesia with a psychological approach with the concept of conformity. The results showed that there were legislative candidates who had received permanent verdicts as corruptors but nominated themselves as legislative members. Psychology approach emphasizes the aspect of mens rea. Simultaneously in addition to a juridical approach in the form of punishment, also a psychological approach in the form of inculcation of local cultural values, and to be effective, real cooperation is carried out between the government, business activists, and academics. RESUMENEl propósito de este estudio es analizar cómo prevenir los candidatos de corrupción mens rea para legisladores en Indonesia con un enfoque psicológico con el concepto de conformidad. Los resultados mostraron que había candidatos legislativos que habían recibido veredictos permanentes como corruptores, pero se nominaban a sí mismos como miembros legislativos. El enfoque psicológico enfatiza el aspecto de mens rea. Simultáneamente, además de un enfoque jurídico en forma de castigo, también un enfoque psicológico en forma de inculcación de valores culturales locales y, para ser efectivo, se lleva a cabo una cooperación real entre el gobierno, los activistas empresariales y los académicos.